1966
DOI: 10.1111/j.1469-8137.1966.tb06367.x
|View full text |Cite
|
Sign up to set email alerts
|

CAMBIAL ACTIVITY IN EUCALYPTUS CAMALDULENSIS DEHN.

Abstract: SUMMARYThe production of xylem and phloem elements by the cambium of Eucalyptus camaldidensis was investigated. Plants grown under various climatic treatments were exposed to '"""CO, for short periods. This treatment left a marker in the xylem and in the phloem cells derived from the cambium during the exposure. Thus, the newly formed cell layers could be counted. Results reveal that the ratio of the number of xylem layers produced to the number of phloem layers produced (4 : i) is practically independent of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
(17 reference statements)
5
5
0
Order By: Relevance
“…Typically, during normal stem growth, XMCs are mitotically more active than PMCs, leading to a disproportionate ratio of xylem to phloem elements, although this varies between species and physiological state. In our experiments, we observed an average ratio of four xylem to one phloem derivative which aligns well with observations by Waisel et al (1966) in Eucalyptus camaldulensis who reported that approximately four xylem derivatives were produced for every one phloem derivative regardless of changes in environmental conditions including photoperiod, thermoperiod, and season. In Populus euramericana , Stahel (1968) observed a ratio of 10:1 during normal growth conditions, and Larson (1994) in a review of this subject presented a selection of xylem/phloem ratios from several tree species and found values that ranged between 15:1 and 1:1.…”
Section: Discussionsupporting
confidence: 92%
“…Typically, during normal stem growth, XMCs are mitotically more active than PMCs, leading to a disproportionate ratio of xylem to phloem elements, although this varies between species and physiological state. In our experiments, we observed an average ratio of four xylem to one phloem derivative which aligns well with observations by Waisel et al (1966) in Eucalyptus camaldulensis who reported that approximately four xylem derivatives were produced for every one phloem derivative regardless of changes in environmental conditions including photoperiod, thermoperiod, and season. In Populus euramericana , Stahel (1968) observed a ratio of 10:1 during normal growth conditions, and Larson (1994) in a review of this subject presented a selection of xylem/phloem ratios from several tree species and found values that ranged between 15:1 and 1:1.…”
Section: Discussionsupporting
confidence: 92%
“…The 1 : 10 phloem to xylem ratio across vein orders found for Populus tremula × alba (Fig. ) matches the annual growth ratio reported for other species of Populus (Evert & Kozlowski, ), and falls within the 1 : 4 to 1 : 10 ratio reported for vascular tissue production in other deciduous temperate trees (Artschwager, ; Waisel et al ., ). The similarity among phloem‐to‐xylem ratios in leaf veins and stems might reflect similar behavior in procambium activity within the entire plant body.…”
Section: Discussionmentioning
confidence: 97%
“…A strictly controlled growth layer formation results in a regular dispersion of the phloem tissue over the entire stem disc. Within one growth layer, the ratio of xylem to phloem tissue is lower compared with trees with conventional secondary growth (ratio: 2 -9; Table 3) (Artschwager, 1950;Waisel et al, 1966;Rajput and Rao, 2000). Besides, they accumulate only a limited number of phloem increments, making the total phloem fraction of an Avicennia stem considerably higher (Esau, 1969).…”
Section: What Triggers Cambium Differentiation?mentioning
confidence: 99%